2018
DOI: 10.1097/aln.0000000000001985
|View full text |Cite
|
Sign up to set email alerts
|

Period-dependent Associations between Hypotension during and for Four Days after Noncardiac Surgery and a Composite of Myocardial Infarction and Death

Abstract: Background The relative contributions of intraoperative and postoperative hypotension to perioperative morbidity remain unclear. We determined the association between hypotension and a composite of 30-day myocardial infarction and death over three periods: (1) intraoperative, (2) remaining day of surgery, and (3) during the initial four postoperative days. Methods This was a substudy of POISE-2, a 10,010-patient factorial-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
163
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(193 citation statements)
references
References 29 publications
5
163
2
4
Order By: Relevance
“…Nonischemic causes, such as hypotension, sepsis, and AF, have also been shown to be more common than ischemic causes. 11,13 We previously reported that left ventricular diastolic dysfunction and intraoperative tachycardia are predictors of PMI, and that AF is a common complication after surgery. 21 Therefore, the use of prophylactic β-blockers before surgery was expected to prevent PMI and associated adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonischemic causes, such as hypotension, sepsis, and AF, have also been shown to be more common than ischemic causes. 11,13 We previously reported that left ventricular diastolic dysfunction and intraoperative tachycardia are predictors of PMI, and that AF is a common complication after surgery. 21 Therefore, the use of prophylactic β-blockers before surgery was expected to prevent PMI and associated adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…10 Indeed, it was recently reported that non-ischemic factors, such as sepsis, tachyarrhythmia, and hypotension, play a greater role than does ischemia. [11][12][13] Beta-blocker treatment has been expected to reduce cardiovascular events after surgery, but a meta-analysis of randomized controlled trials (RCT) suggested that β-blockers reduce non-fatal myocardial infarction but increase stroke and hypotension. 14 The efficacy of perioperative β-blockers, even in high-risk patients, is therefore controversial and current guidelines do not recommend routine use of perioperative β-blockers.…”
mentioning
confidence: 99%
“…15,16 It is assumed that postoperative CPA may be prevented (or delayed) by providing early interventions in response to pre-arrest alarms alerting to potential postoperative cardiovascular or respiratory compromise. 17,18 Early warning scores calculated from vital signs have been used to activate emergency response teams in hospitals in the United Kingdom, Australia, and the United States. 19 In our hospital, the automatic electronic dashboard system (BESTboardÒ) tracks vital signs, in addition to blood chemistry tests including pH, PaCO 2 , PaO 2 , lactic acid, and total CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicates that intraoperative mean arterial blood pressure greater than 65 mmHg reduces the incidence of MINS. (29,30) However, despite good intraoperative blood pressure control, we observed a fairly high rate of MINS in our relatively healthy study population. This emphasizes that even patients with a low estimated cardiac risk having moderate-to high-risk surgery are at risk of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 52%